An IIoT Edge Environment as a Main Support to a 3D Reconstruction Virtualization Application - Badat, Leya; Vidal, Vinicius; Pioli, Laércio; Mehaut, Jean-Francois; Honorio, Leonardo; Dantas, Mario Antonio Ribeiro (Anais do Workshop em Clouds e Aplicações (WCGA), 2020)
This paper describes an experimental research work, which was conducted to gather different types of cameras and computer node, as IIoT (Industrial IoT) devices, to produce support to a digital transformation with a 3D reconstruction virtualization for a real engineering application. The computational approach considered was a heterogeneous edge computing environment. In this environment, different cameras and computer node architectures, collaborate as heterogeneous IIoT processing elements, to provide a better, and as fast as possible, images to a virtualization project. The challenge and complexity related to software packages orchestration, from these IIoT devices, are also reported.